G-TRANE INFORMATION SYSTEM AND EMPLOYEES’ PERFORMANCE AIR FREIGHT DEPARTMENT OF PT NISSIN TRANSPORT INDONESIA - Imam Ozali; Ferdy Tri Whardana (Institut Transportasi dan Logistik Trisakti, 2016)
PT Nissin Transport Indonesia is a freight forwarding company in export and import sector. The main problem of the study is whether G-Trane information system and the employees’ performance influence the productivity of air freight department. The aim of this study is to acknowledge and to analyse the influence of the used information system and the employees’ performance towards the productivity of air freight department. The writer used three methods of collecting data; field research, questionnaire, and library research. Multiple regression analysis, multiple correlation, coefficient determining, as well as hypothesis testing research are used in this study. The result of this study is shown by the multiple linear regression equation of Y= 13.403+0.319 +0.224. , with the coefficient correlation of 0, 64 and determining coefficient of 40,96%. The result of the hypothesis testing research also shows that Fhitung > Ftabel or 4,55 > 3,8, which means Ho is rejected but Ha is accepted. It means there is a positive and significant influence of the G-Trane information system and the employees’ performance towards Air Freight department’s productivity.